A new three phase 6-slots 10-poles permanent magnet flux switching machine with inner rotor configuration - Jenal, Mahyuzie (2021)
Effective use of energy permits industrial and commercial facilities to cut down production costs, boost profits, and stay competitive. Also, the majority of electrical energy consumed in most industrial facilities is used to run electric motors. There has been a recent interest in flux switching motor (FSM) in which all flux sources are stalled in the stator that makes the rotor simple, robust, and brushless. Development of current research, particularly in conventional permanent magnet flux switching machine (PMFSM) has been with toothed rotor structures that employ permanent magnet at the stator that may manipulate the changes of paths for the stator teeth. Still this structure produces less torque and power. Hence, the use of multiple rotor structures has been developed, along with proposed PM configurations, which give significant gains. This research work focused on a new design of PMFSM employing alternate circumferential and radial flux (AlCiRaF) permanent magnet over various rotor poles configuration, optimization based on deterministic method and performance investigation through 2D-FEA. In this work, four topologies have been proposed, such as 6S-10P PMFSM with salient type of rotor (SalR), 6S-10P PMFSM with span rotor (SpR), 6S-8P AlCiRaF PMFSM with segmental rotor (SegR AlCIRaF) and 6S-10P AlCiRaF PMFSM with salient rotor (SalR AlCiRaF) are modeled and simulated using 2D-FEA JMAG v. 14.1 for the initial performance investigation. Since, 6S-10P SalR AlCiRaF has shown higher tendency to achieve better performances compared to conventional design, the model is then undergo further refinement through deterministic optimization method by shifting modeling free parameters in rotor and stator part. Finally, 6S-10P AlCiRaF has achieved better torque, power, speed ranges and efficiency compared with conventional 12Slot-10Pole PMFSM. Besides the optimized 6S-10P AlCiRaF has improved approximately 85.71% of maximum torque and 156% of maximum power than that of initial design machine proving their suitability towards efficient and reliable motors.